High prevalence and clinical characteristics of respiratory infection by human rhinovirus in children from Lima-Peru during years 2009- 2010 - Castañeda-Ribeyro, Ariana (2022)
Introduction Human rhinovirus is a major cause of acute respiratory infections (ARIs) worldwide. Epidemiological data on human rhinovirus (RV) in Peru is still scarce, as well as its role in respiratory infections in children. Therefore, the aim of this study was to describe the prevalence of rhinovirus and to identify the circulating species in nasopharyngeal swabs from children with acute respiratory infections. Materials and methods We analyzed nasopharyngeal swab samples that were collected from children younger than 17 years old, who had a clinical diagnosis of ARI from the "Hospital Nacional Cayetano Heredia"between May 2009 and December 2010. The original study recruited 767 inpatients with ARI, 559 samples of which were included and analyzed in the current study. Detection of rhinovirus and determination of rhinovirus species were characterized by PCR. Results Rhinovirus was detected in 42.22% samples (236/559), RV-A was detected in 10.17% (24/ 236) of the cases, RV-B in 16.53% (39/236), and RV-C in 73.31% (173/236). The age group with the highest number of cases was the 0-5 months group with 45.97%, followed by the 1-5 years group with 25.22%. Most of the positive RV cases, i.e., 86.44% (204/236), were hospitalized. The most common signs and symptoms found in patients who tested positive for RV were cough (72.88%), fever (68.64%), rhinorrhea (68.22%), and respiratory distress (61.44%). Infection with RV-A was associated with wheezing (p = 0.02). Furthermore, RV-C was related to cough (p = 0.01), wheezing (p = 0.002), and conjunctival injection (p = 0.03). A peak in RV-C cases was found in March (32 cases in 2010); June (18 cases in 2009 and 12 cases in 2010), which corresponds to the fall season in Peru; and also November (17 cases in 2009 and 4 cases in 2010), which corresponds to spring. RV-A and RV-B cases were constant throughout the year. Conclusion In conclusion, we found a high prevalence of rhinovirus C infection among pediatric patients with acute respiratory infections in Lima, Peru. This viral infection was more common in children between 0 to 5 months old, and was associated with cough, wheezing, and conjunctival injection. Epidemiological surveillance of this virus should be strengthened/encouraged in Peru to determine its real impact on respiratory infections.